PENGGUNAAN ASAM PERASETAT PADA PROSES DELIGNIFIKASI PULP ACETOSOLV DARI AMPAS TEBU DAN BAMBU BETUNG - Ahmad Sapta Zuidar; Sri Hidayati; Surya Baskita Barus (Jurnal Teknologi & Industri Hasil Pertanian, 2014)
Acetosolv process produced dark pulp because of the high lignin content.  Therefore ,  delignification  process is needed. This process uses peracetic acid to improve pulp qualities. The objective of this research was to determine the effect of different concentrations of peracetic acid against the characteristics of pulp acetosolv from bagasse and bamboo betung.  The research was arranged in a Complete Randomized Block Design with a single treatment and 4 replications.  The treatment used peracetic acid with six levels concentration (9%, 11%, 13%, 15%, 17%, 19%) at a temperature of 85oC for 3 hours. The homogenity and additivity of the data were  analyzed using Bartlett and Tuckey Tests, then they were analyze for ANOVA to see if there is any difference among means, and then processed further using  Least Significant Difference at level of 1% and 5%.  The results showed that the concentration of peracetic acid had significant effect on yield, cellulose, hemicellulose, lignin, and organoleptic color pulp from bagasse and bamboo betung.  The best results showed that the concentration of peracetic acid 15% with cooking duration of  3 hours gave the best pulp. The pulp contained 85.837% of cellulose , 7.757% of hemicellulose , 1.758% of lignin , 73.048% of yield  and  the average organoleptic score for the pulp color was 4.3. Keywords:   acetosolv pulp,  baggase, bamboo,  delignification, paracetic acid